LEGAL STATUS OF THE ADVOCACY INSTITUTION IN UZBEKISTAN (World Bulletin of Management and Law, 2025)
In this article, a deep analysis of the legal status, organizational foundations and the procedure for functioning of the Institute of jurisprudence in the Republic of Uzbekistan is carried out. The principles of legislative regulation of the legal profession, the procedure for entering the profession, independence and adherence to professional ethics are covered. It also reflects on the processes of reforming the lawyer's Office of Uzbekistan, the existing problems and the possibility of using the experience of the International, in particular Germany.